2002
DOI: 10.1016/s0735-1097(02)02382-3
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial neurohormonal profile of spironolactone in severe congestive heart failure

Abstract: Spironolactone administration in patients with CHF has opposite effects on circulating levels of natriuretic peptides (which decrease) and aldosterone and AII (which increase). The reduction in natriuretic peptides might be related to changes in left ventricular diastolic filling pressure and/or compliance, whereas the increase in AII and aldosterone probably reflects activated feedback mechanisms. Further studies are needed to link these changes to the beneficial effects on survival and to determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
83
3
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(103 citation statements)
references
References 27 publications
12
83
3
5
Order By: Relevance
“…Previous reports have shown that BNP levels can be manipulated by therapy and decrease in close relation to the falling of wedge pressures in patients with severe HF under invasive hemodynamic monitoring. [23][24][25][26] In ambulatory patients, there is now a considerable body of evidence showing that ACE inhibitors, angiotensin II receptor 1 antagonists, and spironolactone decrease BNP levels. 21,[23][24][25][26] The decrease of BNP in response to ␤-blockers is observed after 6 to 12 months of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that BNP levels can be manipulated by therapy and decrease in close relation to the falling of wedge pressures in patients with severe HF under invasive hemodynamic monitoring. [23][24][25][26] In ambulatory patients, there is now a considerable body of evidence showing that ACE inhibitors, angiotensin II receptor 1 antagonists, and spironolactone decrease BNP levels. 21,[23][24][25][26] The decrease of BNP in response to ␤-blockers is observed after 6 to 12 months of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] In ambulatory patients, there is now a considerable body of evidence showing that ACE inhibitors, angiotensin II receptor 1 antagonists, and spironolactone decrease BNP levels. 21,[23][24][25][26] The decrease of BNP in response to ␤-blockers is observed after 6 to 12 months of therapy. 27 A pilot study reported that HF therapy guided to decrease NT-proBNP levels is associated with improved prognosis compared with therapy according to clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…The release of renin, an enzyme synthesized, stored, and released by juxtaglomerular cells in the kidney, is stimulated by the sympathetic nervous system, renal artery hypotension, and decreased amounts of sodium delivered to the distal tubules of the kidney. 78,79 After release by juxtaglomerular cells, renin moves into the bloodstream, leading to conversion of the inactive plasma protein angiotensinogen to angiotensin I. Then, angiotensin-converting enzyme converts angiotensin I to angiotensin II.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…Other potent effects of angiotensin II in patients with heart failure are inhibition of the release and reuptake of norepinephrine and increases in circulating levels of antidiuretic hormone, which also increase vasoconstriction and inhibition of water excretion. 78,79 Other important pathophysiological complications due to angiotensin II and aldosterone are release of inflammatory cytokines, activation of macrophages at sites of injury, attraction of neutrophils and macrophages, increased growth of fibroblasts, and synthesis of collagen fibers. Deposition of fibroblasts and collagen results in ventricular hypertrophy and fibrosis of the myocardial wall, leading to inappropriate heart remodeling and subsequent systolic and diastolic ventricular dysfunction.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…That is why serial measurements of biomarkers in the context of WHF may be more valuable than that in the context of chronic HF. For BNP and NT‐proBNP, studies evaluating the influence of treatment on hormone concentrations have shown that therapeutic inhibition of the renin–angiotensin–aldosterone system decreases peptide levels, while beta‐blockade results in an initial increase followed by a decline 31, 32, 33. To reap the full prognostic benefit of repeated measurements, a time frame has to be defined including the point at which re‐measurement of specific biomarker may provide additional information.…”
Section: Discussionmentioning
confidence: 99%